Violet Balestreri Archer (1913-2000) - Hartig, Linda (Music Reference Services Quarterly, 2005)
Violet Archer, one of Canada's well-known composers, passed away in 2000. This article is meant to add biographical information not previously available and to bring closure to her works list. Selected bibliographical citations are also included.
Keywords: Canadian composers; Violet Balestreri Archer